Status of the world's transfrontier protected areas - United Nations Environment Programme World Conservation Monitoring Centre (United Nations Environment Programme-WCMC) (UNEP World Conservation Monitoring Centre (UNEP-WCMC), 2016)
Protected areas that adjoin across international boundaries, referred to in this paper as transfrontier protected areas, provide intriguing possibilities for promoting biodiversity conservation across politically-severed ecosystems and species' home ranges, as well as transfrontier collaborative management which may ultimately contribute to international peace. Since 1932, when Waterton/Glacier was jointly declared the first international peace park by Canada and the United States of America, the concept has gained increasingly widespread recognition and application, particularly in the last decade. The first review of transfrontier protected areas was presented to the Border Parks Workshop held in 1988 during the First Global Conference on Tourism - A Vital Force fi}r Peace.